2020
DOI: 10.2967/jnumed.120.248120
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-Type Plasminogen Activator Receptor (uPAR) PET/MRI of Prostate Cancer for Noninvasive Evaluation of Aggressiveness: Comparison with Gleason Score in a Prospective Phase 2 Clinical Trial

Abstract: The aim of this study was to evaluate the correlation between uptake of the positron emission tomography (PET) ligand 68 Ga-NOTA-AE105 targeting the urokinase-type plasminogen activator receptor (uPAR) and Gleason score in patients undergoing prostate biopsy. Materials & methods: Patients with clinical suspicion of prostate cancer (PCa) or previously diagnosed with PCa were prospectively enrolled in this phase II trial. A combined uPAR PET, multiparametric magnetic resonance imaging (mpMRI) was performed and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…68 Ga-NOTA-AE105 PET has been validated in a phase I study including prostate cancer patients, where uptake of the ligand corresponded to uPAR expression in excised tissue [13]. Additionally, in a recent phase II PET/MRI trial in patients with prostate cancer, we found a clear correlation between tumor uptake of the ligand and Gleason score, which confirmed the ligand as an imaging marker of prostate cancer aggressiveness [14].…”
Section: Introductionsupporting
confidence: 63%
“…68 Ga-NOTA-AE105 PET has been validated in a phase I study including prostate cancer patients, where uptake of the ligand corresponded to uPAR expression in excised tissue [13]. Additionally, in a recent phase II PET/MRI trial in patients with prostate cancer, we found a clear correlation between tumor uptake of the ligand and Gleason score, which confirmed the ligand as an imaging marker of prostate cancer aggressiveness [14].…”
Section: Introductionsupporting
confidence: 63%
“…We included 47 studies that investigated the use of radioligands that target six different receptors of tumor cells for imaging or therapy of PCa patients. The most studied receptors in PCa were gastrin-releasing peptide receptors ( n = 23 studies) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] and the androgen receptor ( n = 11 studies) [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], followed by somatostatin receptors ( n = 6 studies) [ 45 , 46 , 47 , 48 , 49 , 50 ], the urokinase plasminogen activator surface receptor ( n = 4 studies) [ 51 , 52 , 53 , 54 ], the fibroblast activation protein ( n = 2 studies) [ 55 , 56 ] and integrin receptors ( n = 1 study) [ 57 ]. As only phase I and II studies were available, the risk of bias and uncertainty were not assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, immunohistochemical studies have revealed absent to low levels of uPAR expression in healthy homeostatic tissue whereas at the interface between tumor and healthy tissue, uPAR is highly overexpressed on both tumor and tumor-associated stromal cells [8][9][10][11][12]. Such a pattern is ideal for imaging and, not surprisingly, a PET tracer is currently undergoing extensive clinical trials in order to image "cancer aggressiveness" and subsequently aid in tailoring treatment options to disease biology [13].…”
Section: Introductionmentioning
confidence: 99%